Pengaruh Lifestyle Electronic Word Of Mouth dan Brand Image Terhadap Keputusan Pembelian - Eka Sulistiyani; RA. Nurlinda (Universitas 45 Surabaya, 2023)
This study examines the simultaneous and partial effects of Lifestyle, Electronic Word of Mouth, and Brand Image on purchasing decisions. Primary data was collected using the survey method by distributing questionnaires to respondents who subscribe to and watch Netflix. Questionnaires were collected as many as 130 respondents using purposive sampling method. Furthermore, the data is processed using multiple linear regression analysis. Based on the results of the research analysis, it shows that Lifestyle, EWOM and Brand Image together influence purchasing decisions. These results also show that lifestyle and electronic word of mouth have an effect on purchasing decisions, but brand image has no effect on purchasing decisions and EWOM has the most dominant influence on purchasing decisions. The results of this research are expected to be input for Netflix to be able to improve the EWOM marketing strategy so that consumers can be more convincing in making purchasing decisions.